Up-regulation of protective neuronal MicroRNAs by FTY720 and novel FTY720-derivatives. (18th January 2019) - Vargas-Medrano, Javier; Yang, Barbara; Garza, Nathan T.; Segura-Ulate, Ismael; Perez, Ruth G.
Graphical abstract: Highlights: Low dose FTY720 and novel derivatives stimulate microRNA expression in MN9D cells. One microRNA has been demonstrated to reduce cellular alpha-synuclein expression. Other microRNAs have the capacity to reduce neuronal/glial cell death, and/or act on mitochondria. FTY720s thus may have therapeutic potential to reduce neurodegeneration. Abstract: In searching for Parkinson's disease (PD) pharmacotherapies we began studying FTY720, a food and drug administration (FDA) approved drug. We also created derivatives, FTY720-C2 and FTY720-Mitoxy, and began assessing them. Here we treated dopaminergic MN9D cells with FTY720s then measured microRNA (miRNA) levels by PCR arrays. We discovered that all three FTY720s increased miR376b-3p, while FTY720-C2 also increased miR-128-3p, miR-146b-5p, miR-7a-5p, and miR-9-5p, and FTY720-Mitoxy also increased miR-30d-5p. Investigations revealed that some miRNAs downregulate alpha-synuclein, while others reduce apoptosis, suggesting that FTY720s may act to reduce synucleinopathy and dopaminergic neuron loss in PD and related disorders.